2016
DOI: 10.1017/neu.2016.51
|View full text |Cite
|
Sign up to set email alerts
|

A randomised, placebo-controlled trial of transcranial pulsed electromagnetic fields in patients with multiple chemical sensitivity

Abstract: PEMF treatment of 6 weeks showed no effect on functional impairments in MCS. However, a significant decrease in symptom severity was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
5
0
2
Order By: Relevance
“…For example, sham rTMS was shown to reduce [ 11 C] raclopride binding potentials in the striatum of patients with PD, which indicated a placebo induced increase in dopaminergic neurotransmission [ 38 ]. Non-motor placebo effects of T-PEMF performed in other patient populations have also been reported [ 26 , 39 ]. Therefore, although we cannot determine the cause of improvement across groups, we expect the learning effect to be negligible and consider the improvements on CT STS and CT DBP to be a result of the placebo effect.…”
Section: Discussionmentioning
confidence: 91%
“…For example, sham rTMS was shown to reduce [ 11 C] raclopride binding potentials in the striatum of patients with PD, which indicated a placebo induced increase in dopaminergic neurotransmission [ 38 ]. Non-motor placebo effects of T-PEMF performed in other patient populations have also been reported [ 26 , 39 ]. Therefore, although we cannot determine the cause of improvement across groups, we expect the learning effect to be negligible and consider the improvements on CT STS and CT DBP to be a result of the placebo effect.…”
Section: Discussionmentioning
confidence: 91%
“…A new concept is the so-called “Central Sensitivity Syndromes”, which include the MCS, Chronic Fatigue Syndrome and Fibromyalgia, i.e., syndromes with considerable overlap of symptoms and mutual comorbidities [ 27 , 28 ]. These illnesses could have common pathophysiological mechanisms based on central sensitization [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that nasal sprays with hyaluronic acid used to treat olfactory symptoms can improve the well-being of affected study subjects [42]. Transcranial magnetic stimulation has also been shown to improve the symptom burden, while having no effects on functional impairment [43].…”
Section: Characteristics Of Mild Disease and Possible Favorable Factorsmentioning
confidence: 99%